2019
DOI: 10.38055/fs010201
|View full text |Cite
|
Sign up to set email alerts
|

Clothing Fit Issues for Trans People

Abstract: As many as nine million people identify as a transperson in the United States, yet mass clothing designing and manufacturing do not meet the needs of this consumer group. This research examines the role of fit in ready-to-wear (RTW) clothing using qualitative research methods. 90 transpeople from the United States, Canada, and Ireland participated in interviews and data from interviews were analyzed using line-by-line analysis, resulting in three themes. Theme 1 explored current fit problems with RTW clothing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 20 publications
6
22
0
Order By: Relevance
“…These have been shown to positively impact consumer attitude toward products in the attire product category (Argo and Dahl, 2018). Plus, an update to the current clothing sizing and fit system would greatly benefit TGD consumers (Reilly et al , 2019). It is also suggested that privacy while browsing, gender-inclusive changing rooms, gender-inclusive bathrooms (Platt and Milam, 2018) and gender-inclusive clothing sections (Nelson and Hwang, 2021) would create a more inviting atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…These have been shown to positively impact consumer attitude toward products in the attire product category (Argo and Dahl, 2018). Plus, an update to the current clothing sizing and fit system would greatly benefit TGD consumers (Reilly et al , 2019). It is also suggested that privacy while browsing, gender-inclusive changing rooms, gender-inclusive bathrooms (Platt and Milam, 2018) and gender-inclusive clothing sections (Nelson and Hwang, 2021) would create a more inviting atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…Using NVivo versions 11 and 12, all references to clothing were sorted into a single clothing node, including the broad context around the reference. We first identified major groupings including clothing fit issues (Reilly et al, 2019) and critical first exposures to gender (Catalpa & McGuire, 2020). Open coding procedures (Straus & Corbin, 1990) and thematic content analyses, as well as phenomenological approaches (e.g., delineating units of meaning and clustering units of meaning) noted by Creswell (2007), were used for the two prior papers.…”
Section: Methodsmentioning
confidence: 99%
“…Dress can be used to facilitate appearing cisgender and reduce probability of others mistaking gender identity (Catalpa & McGuire, 2020). Research has noted that trans people not only use dress to disguise or draw attention away from incongruent body parts, but to highlight other body parts that align with their gender identity and desired gender presentation (Corwin, 2009; McGuire et al, 2016; Reilly et al, 2019). Rubin (2003) noted that at times TNB people desiring to look cisgender may exaggerate their gender performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Finding clothing that enables expression of gender is a challenge for transgender individuals. Reilly et al (2019) in their research with transgender individuals from Ireland, Canada, and the United States found that participants used clothing to express their gender. Similar to Reddy-Best and Pedersen (2015a), these researchers also identified clothing fit as an issue as fit was key to revealing or concealing body parts that were consistent or inconsistent with their gender.…”
Section: Related Literaturementioning
confidence: 99%